2017
DOI: 10.1016/j.tra.2017.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Easing the traffic: The effects of Indonesia’s fuel subsidy reforms on toll-road travel

Abstract: Indonesia has serious traffic jams. This study uses data from 19 Indonesian toll roads over 2008-2015 to calculate the effects of Indonesia's historic recent fuel subsidy reforms on motor vehicle travel. The timing of the reforms was determined by budgetary and political factors, providing a suitable setting for estimating a causal effect. We control for a broad set of other factors potentially influencing traffic flows. Estimates using monthly data suggest an immediate fuel price elasticity of motor vehicle f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Public transport services have been improved, such as the adoption of the rapid transit bus (TransJakarta) that first began operation in 2004 and rail-based MRT (mass rapid transit), which first operated in 2019. A significant decrease in the fuel subsidy since 2013 is estimated to have lessened the traffic jams in Indonesian cities by 10% [61]. In addition, the Department of Transportation has been investing in pedestrian improvement projects on major thoroughfare streets, such as in Sudirman-Thamrin Street.…”
Section: Path Dependence: Transport-land Use Policies Impact On Jakarmentioning
confidence: 99%
“…Public transport services have been improved, such as the adoption of the rapid transit bus (TransJakarta) that first began operation in 2004 and rail-based MRT (mass rapid transit), which first operated in 2019. A significant decrease in the fuel subsidy since 2013 is estimated to have lessened the traffic jams in Indonesian cities by 10% [61]. In addition, the Department of Transportation has been investing in pedestrian improvement projects on major thoroughfare streets, such as in Sudirman-Thamrin Street.…”
Section: Path Dependence: Transport-land Use Policies Impact On Jakarmentioning
confidence: 99%
“…Our findings also concur with the household survey findings of Wijayapala and Kankanamge (2016) for Sri Lanka, who concluded that electricity subsidies encourage households to use inefficient equipment such as incandescent lamps. Our research complements the work by Burke et al (2017) on the effect of the concurrent reforms to Indonesia's subsidies for gasoline and diesel on traffic flows on Indonesian toll roads.…”
Section: Electricity Subsidy Reform In Indonesiamentioning
confidence: 63%
“…To help finance these investments, Indonesia could replace general price support programs for fuel consumption with subsidies targeted at the poor and near-poor. General price supports have raised fossil fuel consumption and carbon dioxide emissions, congested roads, reduced the cost advantages for investing in energy efficient technologies, and increased fuel imports and thus energy insecurity (see, e.g., Burke et al 2017 ). These funds could be better used investing in the young.…”
Section: Increasing Manufacturing Exportsmentioning
confidence: 99%